INTERVENSI INTEGRATED NEUROMUSCULAR INHIBITATION TECHNIQUE (INIT) DAN TERAPI ULTRASONIK LEBIH MENURUNKAN DISABILITAS LEHER AKIBAT SINDROMA MIOFASIAL OTOT UPPER TRAPEZIUS DIBANDINGKAN INTERVENSI MYOFASCIAL RELEASE TECHNIQUE (MRT) DAN TERAPI ULTRASONIK - Maria, Rita; Pangkahila, Alex; Irfan, M.; Jawi, Made; Griadhi, Adiartha; Lesmana, Indra (Sport and Fitness Journal; Volume 5, No.3, 2017DO - 10.24843/spj.2017.v05.i03.p14, 2017)
The long term use of analgesic drugs in patients with myofascial syndrome had a bad effect. So it is very important to find another methods. Upper trapezius muscle myofascial syndrome is a collection of symptoms such as chronic pain with increased sensitivity to pressure, muscle spasms, tenderness, stiffness, limited motion, and weakness of the upper trapezius muscle. The aim of this study was to compare the rate of decline in the neck disability of interventions for Integrated Neuromuscular Inhibitation Technique (INIT), Myofascial Release Syndrome (MRT), and ultrasound therapy. This research used experimental method with pre-test and post-test group design. This experiment was conducted in RSPI Puri Indah, Jakarta. These samples included 20 people who were divided into two groups of samples, are 10 people in the first group and 10 people in the second group. Samples in the first group had an average age of 30.9 years old with men as much as 4 people and women as much as 6 people. While the second group had an average age of 32.8 years old with men as much as five people and women as many as five people. The results of testing the hypothesis by using test independent sample t-test showed significantly differences between the average after intervention disability first group with mean after intervention disabilities neck second group, with the value of the first group (21.6 ± 4.6)% and the second group (15.6 ± 3.6)% with values p <0.05. It was concluded that the Inhibitation Integrated Neuromuscular Technique (INIT) and ultrasonic therapy was better in reducing the neck disability in the upper trapezius muscle myofascial syndrome, compared to Myofascial Release Syndrome (MRT) and ultrasound therapy. The decline in neck disability will significantly optimize the functional activity of the cervical spine.